Community Development Learning for children with special needs Based on Project Base Learning (Planting Through Aqua Phonics Media & Mobile App) - Siti Anisah; Rahmadhani Fitri; Zuraidah Taro; Rian Farta Wijaya (Community Engagement and Emergence Journal (CEEJ), 2022)
Children with special needs or commonly abbreviated as (ABK) are conditions where children have special characteristics that are different from children in general who experience limitations / extraordinary physical, mental, intellectual, social, and emotional. Special School (SLB) C is one of the schools that treats mentally retarded children. Mental retardation (mental retardation) experiences obstacles and underdevelopment of below-average mental-intellectual development, so that they experience difficulties in completing their tasks. They experience obstacles in behavior and adjustment. These obstacles occur during the developmental period. The problem experienced by partners is the condition of ABK with limitations so that it requires creative and innovative learning methods, especially in increasing creativity and developing the environment for ABK. The main objective of this program is to increase creativity and environmental development (introduction and process of growing vegetable and animal/fish plants) for Children with Special Needs (ABK) through learning with aquaponic media and mobile apps. The educational method provided in this program is about workshops that can increase the creativity of mentally retarded crew members on how to grow plants and raise animals, plants and animals which are used as objects in this service are types of vegetables and fish which are food ingredients , food, which is needed to nourish their daily bodies, so that this introduction can have an impact on increasing ABK's love and concern for the environment